The essence of ontological nihilism and the problem of its overcoming - Sidorenko, Irina N. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The essence of ontological nihilism is revealed such as the world loses its integrity and meaning, and it is argued that the revolt against being has its roots in utopian nihilistic consciousness, which appears as the total will of mind. It is postulated that utopian consciousness has been generated by ontological nihilism replaces creativity with joy of destruction and is as an instrument of violence and reduces everything to a single standard. This is manifested, first, in the extra-rationalization of the political regime; secondly, in the dominance of the technocratic view of the world and the human feeling of its «homelessness»; third, in platitudes, that is, anonymous mind, leading to the triumph of one-dimensional person, who is not able toact and to have personal responsibility. The author of this article substantiates the idea that it is possible to overcome nihilism, but for it needs to return person to his source, through the realization of himself as a historical person, who has resolved to take on the burden of responsibility for this world. The author uses the philosophical ideas of S. Kierkegaard, F. Nietzsche, M. Heidegger, K. Jaspers, H. Arendt, M. Mamardashvili such as a methodological basis of this research.
Keywords: ontological nihilism; nihilistic consciousness; revolt; revaluation of values; will; time; responsibility; fear; guilt; resolve